2022
DOI: 10.1149/1945-7111/ac9343
|View full text |Cite
|
Sign up to set email alerts
|

Hollow FeNi@NCG Materials Prepared with a Double-template Strategy as Highly Efficient Catalysts for Rechargeable Zn-air Batteries

Abstract: One-step pyrolysis approach is the most common used method to synthesize the cathode catalysts of Zn-air batteries (ZABs). However, it is still a challenge to control the structural elements. Herein, a double-template strategy has been established by fabricating GO-doped porous g-C3N4 supported FeNi-MOF arrays as templates to synthesize the FeNi@NCG-700 architecture as highly efficient electrocatalysts. The obtained FeNi@NCG-T catalysts exhibit well-defined hollow architecture with directional arrangement tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…We herein avoid the purely metallic Ni 0 /Fe 0 model typically used for encapsulated catalysts ,,,, and the Ni 1– x Fe x OOH model typically used for fully exposed catalysts. , , Instead, we take an active-site model constituted of an Fe atom sitting on a Ni oxide layer (in the form of FeO 4 or more specifically FeO x H y ; Figure ), which was grown on the fcc-NiFe (111) surface under a strong alkaline condition computationally (i.e., by finding the lowest-energy structure as a series of OH is sequentially introduced to the surface) . Indeed, most X-ray diffraction (XRD) experiments on core–shell catalysts have identified an fcc crystal structure for NiFe metal core before OER operation, and most X-ray spectroscopy (XPS) studies have shown dominant peaks for metallic Ni 0 /Fe 0 on the core surface (unless synthesized with KOH activation), which are gradually oxidized to Ni 2+ /Fe 3+ during the electrochemical cycles. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We herein avoid the purely metallic Ni 0 /Fe 0 model typically used for encapsulated catalysts ,,,, and the Ni 1– x Fe x OOH model typically used for fully exposed catalysts. , , Instead, we take an active-site model constituted of an Fe atom sitting on a Ni oxide layer (in the form of FeO 4 or more specifically FeO x H y ; Figure ), which was grown on the fcc-NiFe (111) surface under a strong alkaline condition computationally (i.e., by finding the lowest-energy structure as a series of OH is sequentially introduced to the surface) . Indeed, most X-ray diffraction (XRD) experiments on core–shell catalysts have identified an fcc crystal structure for NiFe metal core before OER operation, and most X-ray spectroscopy (XPS) studies have shown dominant peaks for metallic Ni 0 /Fe 0 on the core surface (unless synthesized with KOH activation), which are gradually oxidized to Ni 2+ /Fe 3+ during the electrochemical cycles. , …”
Section: Resultsmentioning
confidence: 99%
“…Randomly exposed active sites of these Ni 1– x Fe x OOH catalysts, however, are unstable and eventually dissolve when exposed to harsh electrolytes, keeping these catalysts still inappropriate for long-term operations. Recently, their stabilities and activities have been improved by encapsulating the catalytic nanoparticles with thin graphitic layers, which expose only an optimum amount of active sites to electrolytes (Figure , right). For example, a Ni–Fe bimetallic analogue of Fe­(III) 4 [Fe­(II)­(CN) 6 ] 3 Prussian blue has yielded high-activity-high-stability hybrids between NiFe metal cores and N-doped carbon (NC) shells (NiFe@NC) via a simple pyrolysis, during which the nitrile ligands decompose and form the NC layers encapsulating the metal in core–shell nanostructures. A number of other NiFe@NC core–shell catalysts have also shown enhanced OER activities and stabilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excellent performance was mainly attributed to the following factors: (1) formation of more cobalt active sites and uniform distribution; (2) inserting cobalt ions during the polymerization pyrolysis process, which facilitates the formation of catalytic active sites. Long and colleagues 378 prepared GO‐doped porous g‐C 3 N 4 ‐loaded FeNi‐MOF arrays as templates for the synthesis of FeNi‐MOF@NCG double‐template materials. Then, the hollow FeNi@NCG‐ T ( T = 700°C) architecture, with its directional arrangement, facilitates charge transferred and increases the number of active sites, which could be obtained by calcining the FeNi‐MOF@NCG template at high temperature.…”
Section: The Roles Of G‐c3n4 In Energy Storage Devicesmentioning
confidence: 99%